Predicting Ventricular Arrhythmias in Patients With Ischemic Heart Disease: Clinical Application of the ECG-Derived QRS-T Angle - Borleffs, C Jan Willem; Scherptong, Roderick W.C.; Man, Sum-Che; van Welsenes, Guido H.; Bax, Jeroen J.; van Erven, Lieselot; Swenne, Cees A.; Schalij, Martin J. (Circulation. Arrhythmia and electrophysiology, 2009)
BACKGROUND—In patients with primary prevention implantable cardioverter-defibrillators (ICDs), the incidence of life-threatening ventricular arrhythmias resulting in ICD therapy is relatively low, prompting for better risk stratification. The aim of this study was to assess the value of the QRS-T angle for prediction of ICD therapy and mortality in primary prevention patients with ischemic heart disease. METHODS AND RESULTS—ICD patients (n=412, 361 men; age, 63±11 years) with ischemic heart disease and a left ventricular ejection fraction ≤40% were included. After device implantation, the occurrence of appropriate ICD therapy and mortality was noted. A survival analysis was performed comparing patients with a planar QRS-T angle ≤90° (n=124, 30%) with patients with a planar QRS-T angle >90° before device implantation. Furthermore, patients with a spatial QRS-T angle ≤100° (n=56, 14%) were compared with patients with a spatial QRS-T angle >100°, before implantation. For patients with a planar QRS-T angle >90° as compared with ≤90°, the adjusted hazard ratio for the occurrence of appropriate device therapy was 2.4 (95% CI, 1.1 to 5.2); a spatial QRS-T angle >100° was associated with an adjusted hazard ratio of 7.3 (95% CI, 1.0 to 53.8). Furthermore, a spatial QRS-T angle ≤100° exhibited a positive predictive value of 98% (95% CI, 95 to 100) for the prediction of an appropriate therapy-free follow-up. CONCLUSIONS—A wide QRS-T angle is a strong predictor of appropriate device therapy in primary prevention ICD recipients with ischemic heart disease. Furthermore, a spatial QRS-T angle ≤100° might be of value in the identification of patients in whom, although currently indicated, ICD treatment should be reconsidered.